Afforestation with the Aid of Heavy Soilworking Implements - Monjauze, M. (Indian Forester, 1960)
This paper summarises the Algerian methods of soil working, particularly designed for afforestation practices. It is based on a statement already made before the afforestation Group of the European Forestry Commission functioning under the aegis of the F.A.O. It is envisaged that the principles involved in these methods may be usefully adopted in actual practice. The Metropolitan Forest Service also endorsed this view and proposed to experiment with them in right earnest.